A Control Theory Approach to Understanding the Dynamics of Cognitive Wellbeing - Ioan Susnea; Emilia Pecheanu; Adina Cocu; Paul Iacobescu; Cornelia Tudorie; Simona Susnea (Social Sciences)
(1) Background and Objective: The debate on the stability and variability of subjective wellbeing (SWB) is decades old. However, despite the wealth of literature on this topic, there are relatively few studies that aim to explain the “why” and “how” of the dynamics of SWB. In this context, the objective of this exploratory study is to test the plausibility of a model of the cognitive component of SWB (CWB) inspired by the control theory. In this model, a measure of future life expectations (FLEs) serves as a target in the control loop regulating cognitive wellbeing (CWB), while general self-efficacy (GSE) and affective wellbeing (AWB) are mediators in the direct and feedback loops. (2) Method: To test this model, we collected data from a convenience sample of N-98 Romanian students in Computer Science using well-established questionnaires measuring CWB, GSE, AWB, and FLE. Mediation analyses and path modeling were conducted to evaluate the feedback-based model of the interplay between these variables. (3) Results: The findings confirm a significant relationship between FLE and CWB (β = 0.62, p < 0.001). GSE partially mediates the link between FLE and CWB (β = 0.139, p = 0.02), while AWB mediates the feedback from CWB to FLE (β = 0.297, p < 0.001). The model explains 42% of the variance of CWB. (4) Conclusions: Our study remains exploratory in nature, but preliminary data suggest that a model of SWB based on feedback control is worth attention as it might provide a better understanding of the dynamics of SWB.